How discrimination and perspective-taking influence adolescents' attitudes about justice. (January 2018) - Rasmussen, Hannah F.; Ramos, Michelle C.; Han, Sohyun C.; Pettit, Corey; Margolin, Gayla
Abstract: Little is known about factors influencing adolescents' justice attitudes. This online study investigates perspective-taking and experiences with discrimination for their associations with adolescents' beliefs about how justice is best served. Participants included 179 ethnically/racially diverse high school students ( M age = 16.67 years; SD = 1.02). Higher perspective-taking was associated with less punitive and more restorative attitudes. Youth reporting more personal and ethnic/racial discrimination experiences endorsed more restorative justice attitudes. Perspective-taking also moderated the associations between reports of family, personal, and religious discrimination and punitive justice attitudes: adolescents reporting higher discrimination showed a stronger inverse relationship between perspective-taking and punitive attitudes. Findings have implications for school and community programs aiming to implement restorative policies, and for adolescents' civic participation.